Characterization of the Most Common Diseases in Children Under 5 Years (Pneumonia and Malnutrition): A Correlation Analysis. (2018)
Introduction: In Latin America the nutritional deficit is the most common problem affecting children under 5 years old, which is not an strange issue to Cartagena’ s population, this type of phenomenon is due to lack of nutritional education or food security that leads to appearance of infectious diseases such as pneumonia becoming a public health problem. Objective: To correlate the clinical features of children with malnutrition, pneumonia and malnutrition, and pneumonia from Cartagena de Indias. 2010 to 2012. Methodology: Retrospective cross-sectional descriptive-correlational study. 220 medical records from three groups were analyzed, including 98 children with malnutrition, 100 children with pneumonia and 22 children with malnutrition and pneumonia simultaneously medically attended during 2012-2014. Logistic regression was performed applying Pearson and Durbin Watson calculations with the software SPSS 20.0 ®. Results: Male children have a higher prevalence of malnutrition and pneumonia simultaneously and separately by 63%. The age with more pneumonia and malnutrition cases is in children under 2 years old from stratum I, likewise weight and respiratory problems correlate as common clinical features. Conclusion: It is corroborated the existence of possible signs and symptoms common to pneumonia and malnutrition, in addition the design of dynamic programs that keep into account the environmental conditions.